Cycle and Citation: What Hanne Darboven Calls Thinking*. - Stewart, William (October)
This article analyzes the significance of cyclical forms in the art of Hanne Darboven by reexamining the place of Constructivism and capitalism in her work. It tracks the lasting importance of El Lissitzky for her understanding of the relation between art and mathematics, revealing how Darboven borrowed from Lissitzky a particular interest in oscillatory dynamics. Further, it establishes the influence on Darboven's artistic practice of Georg Christoph Lichtenberg, particularly his method of note-taking—derived from accountants' ledgers—called sudeln. While sudeln works exhibit the oscillatory dynamics described by Lissitzky, they also offers a language for the vast array of citations that Darboven inscribed in her art. The concept of sudeln thus provides a framework for understanding the self-organizing and autopoietic operations that underwrite the paper machines of Darboven's practice. The article concludes by locating this same cyclical, oscillatory form in the most fundamental and abstract of Darboven's gestures, the wavy script that she called Schriftschwünge. In doing so, the article discovers an unexpected emergence of the biographical in Darboven's artworks, notebooks, and letters, in contrast to the anonymous and depersonalized aesthetic with which she is often associated.